Contribuições de egressos de medicina de um centro universitário para a avaliação do curso - Castro, Juliana Corrêa Meziara de (2022)
The construction of pedagogical projects for medical courses should be guided by the National Curriculum Guidelines. After the implementation of the pedagogical project of the course and its progress for 50% of the total workload at most, the request for recognition of the graduation course is mandatory. Thus, until the formation of the first group, the Ministry of Education is in charge of evaluating the Medicine course. The institutional assessment process is also important and must be followed; the internal assessment within the scope of the National College Education Assessment System (SINAES), guided by the Proper Assessment Commission (CPA) and operated by the Institutional Assessment Nucleus, with the participation of the academic community involved, is what takes place at the University Center of Votuporanga (UNIFEV), location of this study. Several instruments and indicators can be built for institutional assessment, with its graduates being part of the enormous challenge of qualifying the process. Currently, at UNIFEV, there is no tool that provides a view of graduates about their profile, that shows how they entered the job market, the contributions that the course brought to their training and the weaknesses that should be diagnosed and corrected. Therefore, the main purpose of this project was to evaluate the profile of the medical professional who graduated at UNIFEV. This is a cross-sectional, descriptive and quantitative study. The population consisted of graduates from 2018 and 2019. A semi-structured questionnaire was applied, with a total of 80 questions, 21 of them open-ended, containing personal data, professional and academic information, complementation of training, implications of academic training in professional life and opinions about integration between the disciplines of the basic areas (basic cycle, first two years) and clinical areas (clinical cycle, two following years), previously tested and validated. The Google Forms survey platform was chosen to apply the survey to participants. This study documented the profile of 114 graduates of the University Center of Votuporanga (UNIFEV) in a pioneering way, with a very representative rate of adherence (80%). It demonstrated the geographic distribution of students, which is more accentuated in the State of São Paulo; greater representation of the female gender (59.6%). All evaluated graduates practice medicine and 92.5% have the profession as their only source of income. Most of them worked in Urgency/Emergency (80%) and in Primary Health Care (65%). There was a significant percentage of graduates who remained at the Institution through student financing (83.3%), but this fact did not have a significant impact on their professional trajectory. Few graduates were enrolled in a medical residency program (35%). Of the evaluated graduates, a large part took a preparatory course for residency during graduation (72.5%). Finally, the desire of most of them to remain close to the educational institution and interest in continuing education programs is highlighted. The study concludes that evaluating the trajectory of former students can provide subsidies to adapt and improve the pedagogical aspects and assistance of medical practice, in addition to subsidizing reflections for the evaluation of the course